2021
DOI: 10.1063/5.0049631
|View full text |Cite
|
Sign up to set email alerts
|

Chimeras confined by fractal boundaries in the complex plane

Abstract: Complex-valued quadratic maps either converge to fixed points, enter into periodic cycles, show aperiodic behavior, or diverge to infinity. Which of these scenarios takes place depends on the map’s complex-valued parameter c and the initial conditions. The Mandelbrot set is defined by the set of c values for which the map remains bounded when initiated at the origin of the complex plane. In this study, we analyze the dynamics of a coupled network of two pairs of two quadratic maps in dependence on the paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Authors in 61 found highly riddled basins in small and highly symmetric all-to-all networks of coupled phase oscillators. Fractal basins of chimeras states were found in small networks of coupled complex maps 62 . In 54 the authors use a low-dimensional description valid for the infinite size system 63 to characterize the basin structure of different patterns in a model of two populations of all-to-all coupled Kuramoto oscillators 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Authors in 61 found highly riddled basins in small and highly symmetric all-to-all networks of coupled phase oscillators. Fractal basins of chimeras states were found in small networks of coupled complex maps 62 . In 54 the authors use a low-dimensional description valid for the infinite size system 63 to characterize the basin structure of different patterns in a model of two populations of all-to-all coupled Kuramoto oscillators 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Chimera states [1][2][3] , which are paradigmatic for the coexistence of synchronization and desynchronization, can be found even in very small, isolated networks 4,5 . Networks in nature, however, often consist of several interacting layers.…”
mentioning
confidence: 99%